Nonwoven fabric using hyaluronate fiber and its manufacturing method

By producing hyaluronate fibers with controlled water content and temperature processing, a nonwoven fabric with enhanced mechanical properties is achieved, addressing production challenges and enabling effective use in medical applications.

JP2025510665AInactive Publication Date: 2025-04-15JINWOO BIO
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2024555279
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-05-23
Filing Date
2022-05-31
Publication Date
2025-04-15
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing methods for producing hyaluronic acid fibers for nonwoven fabrics face issues such as the need for volatile solvent removal, fragile physical properties, low productivity, and high production costs, making commercialization difficult.

Method used

A method involving the preparation of a hyaluronate paste with a specific water content, melting, extrusion through a nozzle, and drying at controlled temperatures to produce hyaluronate fibers with a rough surface, followed by needle-punching to create a nonwoven fabric with high adhesion and tensile strength.

Benefits of technology

The resulting hyaluronate nonwoven fabric exhibits excellent adhesive and tensile strength, suitable for applications like mask packs, tissue repair biomaterials, and adhesion prevention dressings, with improved processing capabilities.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025510665000001_ABST
    Figure 2025510665000001_ABST
Patent Text Reader

Abstract

The present invention relates to a hyaluronate nonwoven fabric using hyaluronate fiber and a manufacturing method thereof, more particularly to a highly functional hyaluronate nonwoven fabric manufactured from hyaluronate fiber having a rough surface and a micro diameter, and a manufacturing method thereof. The manufacturing method of the hyaluronate nonwoven fabric of the present invention is characterized by comprising the steps of (a) manufacturing hyaluronate fiber, (b) curling the manufactured hyaluronate fiber, (c) cutting the curled hyaluronate fiber, (d) forming a web from the cut hyaluronate fiber, and (e) needle punching the formed hyaluronate web. The hyaluronate nonwoven fabric of the present invention contains hyaluronate at a high concentration and is manufactured by needle punching high-strength hyaluronate fiber, and has excellent adhesive strength and tensile strength, so it can be used in various fields such as mask packs for skin external preparations, biomaterials for tissue repair, and adhesion prevention dressings.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a hyaluronate nonwoven fabric using hyaluronate fibers and a manufacturing method thereof, and more particularly to a highly functional hyaluronate nonwoven fabric made of hyaluronate fibers having a rough surface and a micron diameter, and a manufacturing method thereof. [Background technology]

[0002] Nonwoven fabrics are flat fiber structures made by forming a sheet-like web by intertwining various types of fibers, such as natural fibers, chemical fibers, glass fibers, and metal fibers, depending on their respective characteristics, and then bonding them together using mechanical or physical methods. Nonwoven fabrics are widely used in various industrial fields depending on their applications, characteristics, and functions. Furthermore, research is being conducted on various types of nonwoven fabrics by mixing components that can be used for secondary processing or to add various functionalities to nonwoven fabrics.

[0003] Recently, the consumption of products using nonwoven fabrics has been increasing day by day in many industrial fields. For example, nonwoven fabrics are produced into hard panels by high-temperature pressing and are used as finishing materials for automobiles and building materials. Intensive research is being conducted on high-value-added nonwoven fabric products that go beyond simple product purposes and impart high-performance effects in a wide variety of fields such as clothing, hygiene, civil engineering, architecture, automobiles, and medicine. In particular, nonwoven fabric products applied to the medical market are used not only for wearable products such as surgical gowns and masks, but also for surgical drapes, pads, dressings, filter materials, and tissue supports inserted for the regeneration of internal organs.

[0004] Various biodegradable polymers are used to manufacture such medical nonwoven fabrics. Biodegradable polymers are a general term for polymers that undergo gradual chemical decomposition in the body, gradually losing their shape and weight. Representative natural polymers include collagen, fibronectin, gelatin, chitosan, and alginic acid, while synthetic polymers include PLA (poly(lactic acid)), PGA (poly(glycolic acid), PLGA (poly(D,L-lactic-co-glycolic acid) and their similar copolymers, PCL (poly(ε-caprolactone)), polyanhydrides, and polyorthoesters.

[0005] Korean Patent No. 1329261 discloses a functional nonwoven fabric using chitosan and a manufacturing method thereof, and Korean Patent No. 2002586 discloses a thermally bonded nonwoven fabric containing natural fibers in which cellulose fibers are uniformly coated with chitosan.

[0006] Meanwhile, hyaluronic acid (HA) is a mucopolysaccharide present in the dermis layer, and is a biopolymer in which disaccharides consisting of N-acetylglucosamine and D-glucuronic acid linked by β-1,4 glucoside bonds are linked by β-1,3 glucoside bonds to form hyaluronate chains.

[0007] Hyaluronic acid is evenly distributed in connective tissues, epithelium, and nerve tissues of the human body, and is a biocompatible material with various physiological activities, and has been proven to be effective in skin regeneration, moisturizing, maintaining elasticity, and improving wrinkles. For this reason, there has been a recent demand in the industry for manufacturing nonwoven fabrics from such hyaluronate fibers for use in wound dressings, cosmetic patches, anti-adhesion dressings, etc., but the hyaluronic acid fibers used as raw materials for nonwoven fabrics have the following problems depending on the manufacturing method.

[0008] The method for producing hyaluronic acid nanofibers requires an additional removal process of organic solvents such as DMF, DMSO, and formic acid, which are volatile solvents essential in the production of nanofibers. When producing nonwoven fabrics, the nanofiber nonwoven fabric alone is inconvenient to use and has fragile physical properties. In addition, the productivity per unit time is very low, resulting in high production costs.

[0009] To solve this problem, Korean Patent No. 2338355 discloses a method for manufacturing a wet-laid nonwoven fabric, but this method also has weak physical properties and the manufacturing process is somewhat complicated, so research is needed on a more efficient manufacturing method. If the material does not have a certain level of physical properties when used in the form of a nonwoven fabric, processing such as punching for commercialization is impossible, making commercialization difficult.

[0010] Therefore, the inventors have made efforts to solve the above problems, and have found that when a hyaluronate paste with a water content of 50 to 95% by weight is prepared, melted, and then extruded through a nozzle, followed by drying, a large amount of hyaluronate fiber having a rough surface and excellent tensile strength can be produced, and when this fiber is needle-punched, a hyaluronate nonwoven fabric having excellent adhesion and tensile strength can be produced, which has led to the completion of the present invention. Summary of the Invention [Problem to be solved by the invention]

[0011] The object of the present invention is to provide a hyaluronate nonwoven fabric that is effective for use in a mask pack for external skin preparations, a biomaterial for tissue repair, or an adhesion prevention dressing, since it is not only adhesive when used on the skin or inside the body, but also has excellent mechanical properties for processing, and a method for producing the same. [Means for solving the problem]

[0012] In order to achieve the above object, the present invention provides a hyaluronate nonwoven fabric containing hyaluronate fiber, characterized in that, when measured by the following measurement method, the bending angle is 2 to 10°, the moisture content is 5 to 25% by weight, and the hyaluronate content is 90% by weight or more based on the total weight of the fiber excluding moisture.

[0013] <Bending angle measurement method> (a) An HA fiber having a length of 20 cm and a diameter of 1 mm was prepared. (b) 3 cm of one end of the HA fiber was fixed to the top surface of a flat plate. (c) Measure the angle θ between the extension line B of the top surface of the flat plate and the extension line T of the other end of the HA fiber.

[0014] In the present invention, the tensile strength of the hyaluronate fiber is 3 to 15 kg / mm 2 It is characterized in that:

[0015] The present invention is characterized in that the adhesive strength of the hyaluronate nonwoven fabric is 0.9 to 2.7 kPa.

[0016] In the present invention, the hyaluronate nonwoven fabric is characterized in that the thickness is 1 to 10 mm.

[0017] In the present invention, the tensile strength of the hyaluronate nonwoven fabric is 0.3 to 1.5 kg / mm 2 It is characterized in that:

[0018] In the present invention, the hyaluronate nonwoven fabric is characterized in that it is used as a mask pack for external skin preparations, a biomaterial for tissue repair, or an adhesion prevention covering material.

[0019] The present invention also provides a method for producing a hyaluronate nonwoven fabric, comprising the steps of: (a) producing hyaluronate fibers; (b) subjecting the produced hyaluronate fibers to a curling treatment; (c) cutting the curled hyaluronate fibers; (d) forming a web from the cut hyaluronate fibers; and (e) needle punching the formed hyaluronate web.

[0020] In the present invention, the step of producing the hyaluronate fiber includes the steps of: (a-1) preparing a hyaluronate paste by adjusting the water content of a hyaluronate having a weight-average molecular weight of 100-3,000 kDa to 50-95% by weight; (a-2) melting the hyaluronate paste with the adjusted water content at 15-100°C and extruding it through a nozzle; and (a-3) drying the extruded spinning fluid to form fibers.

[0021] In the present invention, when the web is formed, fibers made of a polymer material selected from the group consisting of collagen, fibronectin, gelatin, chitosan, alginic acid, polylactic acid (PLA), polyglutamic acid (PGA), polylactide-glycolide copolymer (PLGA) and polycaprolactone (PCL) are mixed. Effect of the Invention

[0022] The hyaluronate nonwoven fabric of the present invention contains hyaluronate at a high concentration and is produced by needle punching high-strength hyaluronate fibers, and has excellent adhesive strength and tensile strength. [Brief description of the drawings]

[0023] [Figure 1] 1 is a photograph showing the evaluation of the roughness of a hyaluronate fiber according to an embodiment of the present invention (A: smooth hyaluronate fiber, B: rough hyaluronate fiber). [Diagram 2] FIG. 2 is an explanatory diagram showing a method for measuring the bending angle of a hyaluronate fiber according to one embodiment of the present invention. [Diagram 3] 1 is a photograph of a hyaluronate fiber according to an embodiment of the present invention (A: hyaluronate fiber, B: hyaluronate fiber with curls). [Figure 4] 1 is a photograph of a hyaluronate nonwoven fabric manufactured by needle punching according to an embodiment of the present invention. [Diagram 5] 1 is a photograph of a hyaluronate and chitosan mixed nonwoven fabric according to an embodiment of the present invention. [Figure 6] Photographs of the microstructure of the needle-punched nonwoven fabric of the present invention (A: hyaluronate nonwoven fabric, B: hyaluronate and chitosan mixed nonwoven fabric). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0024] In the present invention, it was confirmed that when a hyaluronate paste with a moisture content adjusted to a specific range is spun from a nozzle at a certain temperature and dried at a high temperature instead of at room temperature, a hyaluronate fiber with a very rough fiber surface can be produced, and when this is needle punched, a nonwoven fabric with excellent adhesion and mechanical strength can be produced.

[0025] In the present invention, the moisture content of the hyaluronate is adjusted to 50-95% by weight to prepare a paste, the hyaluronate paste is melted at a temperature of 15-100°C, extruded through a nozzle, and then dried at 100-150°C to obtain a paste with a moisture content of 5-25% by weight and a viscosity of 3-15 kg / mm 2The hyaluronate fiber was heated to curl it, then cut to a certain length, and a web was formed by carding and air-laid processes. The web was then needle-punched to form a nonwoven fabric, which was then compressed to produce a nonwoven fabric with excellent adhesion and tensile strength.

[0026] Therefore, the present invention relates to a method for producing a hyaluronate nonwoven fabric, comprising the steps of: (a) producing hyaluronate fibers; (b) curling the produced hyaluronate fibers; (c) cutting the curled hyaluronate fibers; (d) forming a web from the cut hyaluronate fibers; and (e) needle punching the formed hyaluronate web.

[0027] In the present invention, the step of producing the hyaluronate fiber includes: (a-1) preparing a hyaluronate paste by adjusting the water content of a hyaluronate having a weight average molecular weight of 100-3,000 kDa to 50-95% by weight; (a-2) melting the hyaluronate paste with the adjusted water content at 15-100°C and extruding it through a nozzle; and (a-3) drying the extruded spinning fluid to form a fiber.

[0028] In the present invention, the hyaluronate is a salt bound to hyaluronic acid, and examples thereof include, but are not limited to, sodium hyaluronate, calcium hyaluronate, and potassium hyaluronate.

[0029] In the present invention, the molecular weight of the hyaluronate is preferably 100 to 3,000 kDa. The water content of the hyaluronate in the hyaluronate paste is preferably 50 to 95% by weight.

[0030] The hyaluronate paste can be prepared by adding a solvent to the hyaluronate. It is preferable to use water or an aqueous ethanol solution as the solvent and mix until the solvent is uniformly mixed.

[0031] In order to facilitate the mass spinning process, the water content of the hyaluronate paste may be 50-95% by weight, preferably 88-92% by weight. If the water content is less than 50% by weight, high pressure is required during spinning, and if the water content is more than 95% by weight, the hyaluronate paste is in a liquid form rather than a paste, which can cause problems such as breakage of the thread during spinning.

[0032] The present invention is characterized in that after the preparation of the hyaluronate paste, a step of leaving it at 0-100°C for 6-12 hours for water equilibrium is carried out. If the temperature and time are outside the above ranges, the water equilibrium is not properly carried out. The water equilibrium is for the purpose of uniformly mixing the water molecules and hyaluronic acid in the paste, and if spinning is carried out without water equilibrium, the water molecules and hyaluronic acid are not uniformly mixed, and therefore it becomes impossible to spin at a constant speed during spinning.

[0033] In the present invention, the hyaluronate paste with a water content adjusted to 50-95% by weight is put into a spinning device, melted at 15-100°C, and then extruded through a nozzle to produce a spinning fluid. At this time, if the temperature is less than 15°C, the hyaluronate paste is not melted and cannot be extruded, and if the temperature exceeds 100°C, the dough will boil.

[0034] In the present invention, the extruded spinning fluid is dried to finally form a fiber, and the drying is preferably performed at 100 to 150° C. depending on the moisture content of the paste. If the drying temperature is less than 100° C., the surface of the produced fiber is smooth, so that the entanglement force in the needle punching process after the web formation is weak, making it difficult to form a nonwoven fabric, and if the drying temperature exceeds 150° C., there is a problem that the fiber browns and cracks occur.

[0035] The produced hyaluronate fiber can be produced with a hyaluronate content of 90% by weight or more, a water content of 5-25% by weight, and a tensile strength of 3-15 kg / mm 2 Since the surface of the fiber is very rough, nonwoven fabrics having various densities and physical properties can be produced using the fiber.

[0036] The method for producing a hyaluronate nonwoven fabric of the present invention is characterized in that the produced fibers are curled by heat treatment or the like to increase the crossing force between the fibers. In the case of heat treatment, the hyaluronate fibers can be curled by treating them with hot air at a high temperature of 70°C or higher.

[0037] In order to form a web for producing a nonwoven fabric, the produced hyaluronate fiber is cut to a desired length, and the cut hyaluronate fiber is dispersed by air pressure, and then the resulting dispersion is extruded by air pressure in a carding and airlaid process to form a web.

[0038] The needle punching step of the present invention is a step of punching the flat sheet-like web with needles. Specifically, the needle punching step is a step of repeatedly moving a needle plate to which needles are attached up and down when passing through a needle loom, thereby combining a part of the two-dimensional random fiber arrangement into a three-dimensional random structure, thereby producing a nonwoven fabric.

[0039] The method for producing a hyaluronate nonwoven fabric of the present invention allows for the mixing of fibers made of biocompatible materials when forming a web. That is, in order to ensure a wider variety of physical properties and functionality, hyaluronate fibers can be mixed with collagen, fibronectin, gelatin, chitosan, alginic acid, polylactic acid (PLA), polyglutamic acid (PGA), polylactide-glycolide copolymer (PLGA), polycaprolactone (PCL), and other pharmacologically acceptable biocompatible materials that can be produced into fibers.

[0040] From another viewpoint, the present invention relates to a hyaluronate nonwoven fabric containing hyaluronate fiber, characterized in that, when measured by the following measurement method, the bending angle is 2 to 10°, the moisture content is 5 to 25% by weight, and the hyaluronate content is 90% by weight or more based on the total weight of the fiber excluding moisture.

[0041] <How to measure bending angle> (a) An HA fiber having a length of 20 cm and a diameter of 1 mm was prepared. (b) 3 cm of one end of the HA fiber was fixed onto the top surface of a flat plate. (c) Measure the angle θ between the extension line B of the top surface of the flat plate and the extension line T of the other end of the HA fiber.

[0042] The tensile strength of the hyaluronate fiber is 3 to 15 kg / mm 2 Therefore, it is possible to manufacture nonwoven fabrics by needle punching. If the tensile strength of hyaluronate fiber is 3kg / mm 2 If it is less than 15kg / mm, the fiber may break and processing may be difficult. If the tensile strength of the hyaluronate fiber is less than 15kg / mm 2 If it exceeds this value, the material will be hard, which may cause inconvenience in use after production into a nonwoven fabric.

[0043] The hyaluronate nonwoven fabric of the present invention preferably has a thickness of 1 to 10 mm, and the nonwoven fabric produced has a loading capacity of 0.3 to 1.5 kg / mm ​​depending on the thickness of the nonwoven fabric. 2and an adhesive strength of 0.9 to 2.7 kPa.

[0044] The hyaluronate nonwoven fabric of the present invention has excellent adhesive strength and tensile strength, and can therefore be used for applications such as mask packs for external skin preparations, biomaterials for tissue repair, and adhesion prevention covering materials. [Mode for carrying out the invention]

[0045] The present invention will be described in more detail below with reference to examples. It will be obvious to those skilled in the art that these examples are merely for illustrating the present invention and are not intended to limit the scope of the present invention.

[0046] <Example 1: Preparation of hyaluronate paste> Sodium hyaluronate with a molecular weight of 150 kDa (Hi-Aqua TM The hyaluronate paste was prepared by adding water to the hyaluronate solution (Jinwoo Bio Co., Ltd.) and mixing and kneading it to prepare a hyaluronate paste with a water content of 50 to 95% by weight. The prepared hyaluronate paste was stored in a refrigerator at 4°C for 12 hours to induce water equilibrium.

[0047] Example 2: Production of hyaluronate fibers by spinning The hyaluronate paste produced in Example 1 was placed in the storage section of a spinning device, melted at 15 to 100°C, pressurized and spun through a nozzle, and dried at 120°C to produce hyaluronate fibers with a moisture content of 5 to 25% by weight.

[0048] Comparative Example 1: Production of hyaluronate fiber by spinning The hyaluronate paste produced in Example 1 was placed in the storage section of a spinning device, melted at 15 to 100°C, pressurized and spun through a nozzle, and dried at 50°C to produce hyaluronate fibers with a moisture content of 5 to 25% by weight.

[0049] <Comparative Example 2: Production of hyaluronate fiber by spinning> The hyaluronate paste produced in Example 1 was placed in the storage section of a spinning device, melted at 15 to 100°C, pressurized and spun through a nozzle, and dried at 160°C to produce hyaluronate fiber.

[0050] <Experimental Example 1: Evaluation of fiber roughness depending on drying temperature of hyaluronate fiber> The surface roughness of the fibers produced in Example 2, Comparative Example 1, and Comparative Example 2 was evaluated under a microscope (FIG. 1).

[0051] As a result, fibers with a moisture content of 5-25 wt% were spun under drying conditions of 50°C (Comparative Example 1) and 120°C (Example 2), but the fibers dried at 50°C had a smooth surface, while the fibers dried at 120°C had a rough surface. Comparative Example 2, where the drying temperature was 160°C, had a moisture content of 1-5 wt%, and it was confirmed that the fibers browned and cracked excessively.

[0052] <Experimental Example 2: Measurement of bending angle of hyaluronate fiber> The bending angle of the hyaluronate fiber produced in Example 2 was measured by the following method (see FIG. 2), and the results are shown in Table 1.

[0053] (a) An HA fiber having a length of 20 cm and a diameter of 1 mm was prepared. (b) 3 cm of one end of the HA fiber was fixed onto the top surface of a flat plate. (c) Measure the angle θ between the extension line B of the top surface of the flat plate and the extension line T of the other end of the HA fiber.

[0054] [Table 1]

[0055] As can be seen from Table 1, when the moisture content of the hyaluronate fiber exceeds 25% by weight, the bending angle exceeds 10°, making it difficult to form a web or manufacture a nonwoven fabric by needle punching, and even if a nonwoven fabric is manufactured, the physical properties are deteriorated, making it impossible to perform processing such as punching for commercialization, and thus it is determined that there is a problem with commercialization.

[0056] Furthermore, it was confirmed that when the water content of the hyaluronate fiber is less than 5% by weight, the fiber maintains its shape, but is hard and inflexible, and therefore easily breaks.

[0057] In contrast, when the moisture content of the hyaluronate fiber is 5 to 25% by weight, the bending angle is 2 to 10°, and it was found that the hyaluronate fiber has a form suitable for producing nonwoven fabrics by needle punching.

[0058] <Experimental Example 3: Measurement of tensile strength of hyaluronate fiber> The tensile strength of the hyaluronate fiber produced in Example 2 was measured, and the results are shown in Table 2. The tensile strength was measured using a universal material testing machine with a 5 cm long sample attached to a test fixture and a crosshead speed of 2 mm / min.

[0059] [Table 2]

[0060] From Table 2, it was determined that when the moisture content of the hyaluronate fiber is 50% by weight or more, the tensile strength drops sharply, the fiber becomes prone to breakage, and the fiber loses elasticity, preventing it from performing its functions properly.

[0061] Furthermore, when the water content of the hyaluronate fiber was 5% by weight or less, the fiber shape was maintained, but it was so hard that it easily broke, and the tensile strength could not be measured.

[0062] In contrast, when the water content of the hyaluronate fiber is 5 to 25% by weight, the tensile strength is 3.24 to 13.38 kg / mm 2 It was found that the hyaluronate fiber can realize the shape and function of a thread.

[0063] <Example 3: Production of hyaluronate nonwoven fabric by needle punching> 1) Manufacturing of hyaluronate fiber Using the method of Example 2, a hyaluronate fiber (tensile strength: 3-15 kg / mm) having a bending angle of 2-10°, a moisture content of 5-25% by weight, and a hyaluronate content of 90% by weight or more based on the total weight of the fiber excluding moisture was obtained. 2 ) was produced (Figure 3A).

[0064] 2) Curling process The produced hyaluronate fiber was treated with hot air at 70 to 100°C to produce curled hyaluronate fiber (Figure 3B).

[0065] 3)Cutting The curled hyaluronate fibers were cut into fixed lengths of 3 to 7 cm using a cutting machine.

[0066] 4) Web formation by carding and airlaid The chopped hyaluronate fibers were dispersed by air pressure and then extruded by air pressure to form a web.

[0067] 5) Needle punching A uniform nonwoven fabric (average thickness 5 mm) was produced from the multi-layer sheet formed from the web by a needle punching process (Figure 4).

[0068] <Comparative Example 3: Production of hyaluronate nonwoven fabric by needle punching> The method of Comparative Example 1 was used to produce hyaluronate fibers (tensile strength: 3-15 kg / mm) having a bending angle of 2-10°, a moisture content of 5-25% by weight, and a hyaluronate content of 90% by weight or more based on the total weight of the fiber excluding moisture. 2 ) was prepared and used to prepare a hyaluronate nonwoven fabric in the same manner as in Example 3.

[0069] As a result, it was found that when hyaluronate fibers with a smooth surface are used, the strength with which the fibers intertwine during the needle punching process after the formation of the web is weak, and therefore a good nonwoven fabric is not formed.

[0070] Example 4: Production of nonwoven fabric containing hyaluronate and chitosan by needle punching 1) Manufacturing of hyaluronate fiber The method of Example 2 was used to obtain hyaluronate fibers (tensile strength: 3-15 kg / mm) having a bending angle of 2-10°, a moisture content of 5-25% by weight, and a hyaluronate content of 90% by weight or more based on the total weight of the fiber excluding moisture. 2 ) was manufactured.

[0071] 2) Chitosan fiber Manufacturer: Saturn Biotech, diameter 0.006~0.018mm

[0072] 3) Curling process Hyaluronate fibers were treated with hot air at high temperatures of 70 to 100°C to produce curled hyaluronate fibers.

[0073] The chitosan fibers were heat-treated with steam at 100°C or higher, or in the same manner as for hyaluronate, to produce curled chitosan fibers.

[0074] 4)Cutting The curled hyaluronate and chitosan fibers were cut into fixed lengths of 3 to 7 cm using a cutting machine.

[0075] 5) Web formation by carding and airlaid, and needle punching The cut hyaluronate fiber and chitosan fiber were mixed in a 50:50 weight percent ratio and processed in the same manner as in Example 3 to finally produce a nonwoven fabric (average thickness 5 mm) containing a mixture of hyaluronate and chitosan (Figure 5).

[0076] <Experimental Example 4: Confirmation of the microstructure of nonwoven fabric> The microstructure of the hyaluronate nonwoven fabrics produced in Examples 3 and 4 was confirmed using a microscope (CX33RTFS2, Olympus Corporation, Korea) (Figure 6). A web-type nonwoven fabric structure with cross-links between fibers was confirmed. In particular, in the case of the nonwoven fabric mixed with chitosan, it was confirmed that the hyaluronate fiber and the chitosan fiber were well mixed. Compared to nonwoven fabrics made by wet spinning, web-type nonwoven fabrics have spaces between the cross-links between fibers, and therefore have the characteristics of being more excellent in physical properties and easier to process and use.

[0077] <Experimental Example 5: Measurement of gelation degree of hyaluronate nonwoven fabric> The gelation degree of the needle-punched pure hyaluronate nonwoven fabric (Example 3) and the nonwoven fabric containing 50% by weight each of hyaluronate and chitosan (Example 4) was measured as follows.

[0078] The nonwoven fabric of pure hyaluronate and the nonwoven fabric of hyaluronate and chitosan, each containing 50% each, were immersed in purified water for 5 seconds, then taken out to remove the moisture from the outside of the nonwoven fabric, and then weighed to measure the gelation degree. The gelation degree was calculated as follows:

[0079] Degree of gelation (%) = (weight after gelation - weight before gelation / weight before gelation) x 100

[0080] [Table 3]

[0081] It was found that the nonwoven fabric containing chitosan had a lower gelling degree than the nonwoven fabric containing pure hyaluronate because of its very low solubility in water.

[0082] <Experimental Example 6: Adhesive strength test of hyaluronate nonwoven fabric> Using a Texture Analyser (TA) (QM100SN, Qmesys Co. Ltd., Korea), the adhesive strength of a needle-punched pure hyaluronate nonwoven fabric (Example 3, pure hyaluronate nonwoven fabric with a moisture content of 25% by weight) and a nonwoven fabric containing 50% each of hyaluronate and chitosan (Example 4, hyaluronate+chitosan nonwoven fabric with a moisture content of 25% by weight, 50:50 by weight ratio) was measured as follows.

[0083] Pigskin was cut into 3x3cm rectangles, left in room temperature water for 24 hours to adjust the moisture content to 22.3%, and then attached to the upper and lower probes of a TA (Texture Analyzer). A 2x2cm rectangular nonwoven fabric of pure hyaluronate, a nonwoven fabric mixed with chitosan, and a nonwoven fabric made of chitosan only were placed on the lower pigskin, pressed at 3.2kPa for 3 minutes, and then peeled off at a speed of 10mm / min to measure the adhesive strength.

[0084] [Table 4]

[0085] It was confirmed that the nonwoven fabric made of pure chitosan had no adhesive strength, whereas the nonwoven fabric made of pure hyaluronate had higher adhesive strength than the nonwoven fabric mixed with chitosan, because the degree of gelation was higher, which increased adhesive strength.

[0086] It was also found that a certain degree of adhesive strength was observed even in the case of side effects mixed with chitosan.

[0087] As a result, it was found that by mixing appropriate amounts of hyaluronate and chitosan to manufacture a nonwoven fabric, it is possible to manufacture a nonwoven fabric with high physical properties by adjusting the gelation degree to control the duration in the body and by imparting targeting ability by imparting adhesiveness.

[0088] <Experimental Example 7: Measurement of tensile strength of hyaluronate nonwoven fabric> The tensile strength of the pure hyaluronic acid salt nonwoven fabric (Example 3, pure hyaluronate nonwoven fabric with a water content of 25% by weight) and the nonwoven fabric containing 50% each of hyaluronate and chitosan (Example 4, hyaluronate+chitosan nonwoven fabric with a water content of 25% by weight, 50:50 by weight ratio) was measured by needle punching, and the results are shown in Table 5. The tensile strength was measured by mounting a sample with a length of 5 cm on a test fixture and using a universal material testing machine with a crosshead speed of 2 mm / min.

[0089] [Table 5]

[0090] From Table 5, it can be seen that when chitosan fiber is mixed with pure hyaluronate fiber, it shows higher tensile strength. When chitosan fiber is mixed during the formation of nonwoven fabric, it shows stronger bonding strength because the chitosan fiber is entangled between the hyaluronate nonwoven fabric.

[0091] Although the specific parts of the present invention have been described in detail above, it is clear to those skilled in the art that such specific descriptions are merely preferred embodiments and do not limit the scope of the present invention. Therefore, the substantial scope of the present invention should be defined by the appended claims and their equivalents. [Industrial Applicability]

[0092] The hyaluronate nonwoven fabric of the present invention has excellent adhesive strength and tensile strength, and can be used in a variety of fields, such as mask packs for external skin preparations, biomaterials for tissue repair, and adhesion prevention dressings.

Claims

1. A hyaluronate nonwoven fabric containing hyaluronate fiber, characterized in that, when measured by the following measurement method, the bending angle is 2 to 10°, the moisture content is 5 to 25% by weight, and the hyaluronate content is 90% by weight or more based on the total weight of the fiber excluding moisture. <Bending angle measurement method> (a) Prepare an HA fiber having a length of 20 cm and a diameter of 1 mm. (b) 3 cm of one end of the HA fiber was fixed onto the upper surface of a flat plate. (c) Measure the angle (θ) between the extension line (B) of the top surface of the flat plate and the extension line (T) of the other end of the HA fiber.

2. The tensile strength of the hyaluronate fiber is 3 to 15 kg / mm 2 The hyaluronate nonwoven fabric according to claim 1, characterized in that

3. The hyaluronate nonwoven fabric according to claim 1, characterized in that the adhesive strength of the hyaluronate nonwoven fabric is 0.9 to 2.7 kPa.

4. The hyaluronate nonwoven fabric according to claim 1, characterized in that the thickness of the hyaluronate nonwoven fabric is 1 to 10 mm.

5. The tensile strength of the hyaluronate nonwoven fabric is 0.3 to 1.5 kg / mm 2 The hyaluronate nonwoven fabric according to claim 1, characterized in that

6. The hyaluronate nonwoven fabric according to claim 1, which is used as a mask pack for external skin preparations, a biomaterial for tissue repair, or an adhesion prevention covering material.

7. (a) producing hyaluronate fibers; (b) subjecting the produced hyaluronate fiber to a curling treatment; (c) cutting the curled hyaluronate fiber; (d) forming a web from the cut hyaluronate fibers; (e) needle-punching the formed hyaluronate web.

8. The step of producing hyaluronate fibers comprises: (a-1) preparing a hyaluronate paste by adjusting the water content of a hyaluronate having a weight average molecular weight of 100 to 3,000 kDa to 50 to 95% by weight; (a-2) melting the hyaluronate paste having a controlled water content at 15 to 100°C and then extruding it through a nozzle; (a-3) drying the extruded spinning fluid to form fibers.

9. The tensile strength of the produced hyaluronate fiber is 3 to 15 kg / mm 2 The method for producing a hyaluronate nonwoven fabric according to claim 7, characterized in that

10. The method for producing a hyaluronate nonwoven fabric according to claim 7, characterized in that when forming the web, fibers made of a polymer material selected from the group consisting of collagen, fibronectin, gelatin, chitosan, alginic acid, polylactic acid (PLA), polyglutamic acid (PGA), polylactide-glycolide copolymer (PLGA) and polycaprolactone (PCL) are mixed.

Citation Information

Patent Citations

  • Preparation method of medicament-loaded biodegradable nano-fiber medical dressing

    CN102068339B

  • Air-permeable hydrophilic composite fabric and preparation method thereof

    CN109355916A

  • Nonwoven material composed of hyaluronic acid derivative

    JP1995502430A

  • Threads made of hyaluronic acid and / or its derivatives, methods for producing the same, and their use

    JP2012501391A

  • Hyaluronan fibers, their preparation method and use

    JP2014502678A